Improving the Quality of Service and Inter-Individual Communication on E-commerce Consumer Satisfaction - LUWIHA, LUWIHA; Nagatirtha, Partama; Meyliana, Henny; Karsinah, Karsinah; Saputri, Vike Aprilianin Marwintaria (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2023)
The general objective of this research is to determine whether or not there is an influence of interpersonal communication and service quality on consumer satisfaction. The research hypothesis is that there is an influence of interpersonal communication and service quality on customer satisfaction. The subject of this research is consumers who use e-commerce. The subjects of this study consisted of men and women aged 18-23 years, totaling 60 people at the time of the trial and 60 people at the time of data collection. The data collected through the scale is then distributed to the research subjects. The data were then analyzed statistically using multiple regression analysis with SPSS version 16.0 for Windows. The analysis results obtained the value of R = 0.777 with p = 0.000 (p <0.01). The magnitude of the coefficient of determination (R-Square) of interpersonal communication and service quality on customer satisfaction is 60.3% (0.603). The general conclusion from this study is that there is a very significant positive influence between interpersonal communication and service quality on customer satisfaction. The higher the interpersonal communication skills and the quality of service employees provide, the higher the customer satisfaction.